Cochrane Database of Systematic Reviews 2016
DOI: 10.1002/14651858.ed000116
|View full text |Cite
|
Sign up to set email alerts
|

The end of the wormwars?

Abstract: Aiken et al. (2014) usefully correct some errors in Miguel and Kremer (2004). Miguel and Kremer (2004) made two key claims: 1) deworming creates positive epidemiological externalities, thus causing estimates of the impact of deworming based on individual randomization to be biased downwards; and 2) deworming increases school participation. The results in Aiken et al. (2014) are consistent with these findings. In addition to direct impacts of deworming treatment on worm infections, Aiken et al. (2014) find exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…between the Campbell and Cochrane reviews here could hardly be stronger. 7 The additional network and subgroup analyses in the Campbell review fi nd no evidence of spillover eff ects, no synergistic eff ects of co-interventions, and no evidence regarding any moderating impact of worm burden or the learning environment. 5 Welch and colleagues encourage a further analysis using individual patient data analysis of deworming trials, although substantive new insights seem unlikely given the evidence of ineff ectiveness for most outcomes across multiple analyses.…”
Section: Comment E3mentioning
confidence: 97%
See 1 more Smart Citation
“…between the Campbell and Cochrane reviews here could hardly be stronger. 7 The additional network and subgroup analyses in the Campbell review fi nd no evidence of spillover eff ects, no synergistic eff ects of co-interventions, and no evidence regarding any moderating impact of worm burden or the learning environment. 5 Welch and colleagues encourage a further analysis using individual patient data analysis of deworming trials, although substantive new insights seem unlikely given the evidence of ineff ectiveness for most outcomes across multiple analyses.…”
Section: Comment E3mentioning
confidence: 97%
“…Welch and colleagues' review is a thorough and substantive replication of the Cochrane review, 6,7 with additional sophisticated analyses and adjustments that take into account criticisms levelled by deworming advocates at the current Cochrane edition that we author. Since the fi rst edition 8 of the Cochrane review in 2000, advocates of deworming have ignored, ridiculed, or attacked the various editions.…”
mentioning
confidence: 99%
“…A second independent Campbell review confirmed the findings of the Cochrane Review (Welch 2017). In a commentary on these reviews, Tovey and colleagues stated that while Cochrane and Campbell have developed policies and processes to limit duplication of e orts, given the contentious nature of this particular question, replication was deemed necessary and justified (Tovey 2016).…”
Section: Description Of the Problem Or Issuementioning
confidence: 99%
“…Replication can also serve to purposefully broaden or narrow the research question in existing reviews, particularly for questions that may address sizable benefits or harms. When a Cochrane review on mass deworming was criticized for not including long-term educational and labour outcomes from non-randomized studies, a Campbell replication review extended the scope of the original review and confirmed its findings ( 4 , 5 ). These examples highlight the potential value of planned and purposeful systematic review replication.…”
mentioning
confidence: 95%